2013
DOI: 10.1007/s00268-013-2211-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Chemical Component Paralysis Using Botulinum Toxin for Incisional Hernia Repairs

Abstract: Despite similar multimodality treatment of postoperative pain after IHR, patients who underwent CCP required significantly less opioid analgesia and reported less pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 30 publications
3
67
1
9
Order By: Relevance
“…BTA was administered through 3 16,17 or 5 18–21 injection sites on each side of the abdomen. The administered total doses were 100 U 18,21 , 300 U 16,17 , and 500 U 19,20 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BTA was administered through 3 16,17 or 5 18–21 injection sites on each side of the abdomen. The administered total doses were 100 U 18,21 , 300 U 16,17 , and 500 U 19,20 .…”
Section: Resultsmentioning
confidence: 99%
“…The administered total doses were 100 U 18,21 , 300 U 16,17 , and 500 U 19,20 . Four studies reported that BTA was diluted with 0.9% saline before administration to the following final concentrations: 2 U/ml 16,17 , 50 U/ml 21 , or 100 U/ml 19 . The BTA dilution was then divided into 6 16,17 to 10 18–21 equal doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Botox® in patients with incisional hernia repair has also shown to significantly improve pain scores and reduce need for opioid analgesia. 49, 50 …”
Section: Discussionmentioning
confidence: 99%
“…The search for painless hernia surgery has resulted in some interesting work by Zendejas and his group, published in this issue of the World Journal of Surgery [1]. Botulinum toxin A (Botox), a potent muscle-paralyzing agent, is commonly used for various medical and cosmetic indications.…”
Section: I've Never Been To a Botox Party…mentioning
confidence: 99%